Effect of Zinc Application Biofortification of Zn in Grain of Chickpea (Cicer arietinum L.) Varieties - Meral A. Koca; M. Sait Adak (Recent Progress in Plant and Soil Research Vol. 1, 2021)
The purpose of this study was to investigate the response some chickpea varieties to zinc fertilization. In other words to enrich the zinc (an essential element) content of chickpea grain by fertilization. Because of the lack of zinc not only leads to a reduction in product yield, but also a reduction in quality. Fertilizer application is one of the important agricultural approaches to increase the quality. We hypotheized that different chickpea varieties were fertilized with zinc and compared with control in a two-year study under rainfed field conditions, as well as farmer cultivation. A randomized complete block experimental design in split plot arrangements with three replications was used. Ten chickpea varieties as main plots and zinc treatments as split plots were selected. According to obtained results there were significant differences among its varieties. For instance, in 2012 the best result was obtained from zinc application of Uzunlu-99 variety with 51.00 mg kg-1 and in 2013 the best outcome was obtained from zinc application of 64.33 mg kg-1 ILC-195. And also our findings provided that zinc fertilizing a crops such a chickpea for better biofortification under zinc poor soils. When the average values were taken into consideration, our experiment concludes that the concentration of zinc in grain increased with zinc fertilizer application.